FAKTOR-FAKTOR DALAM MENENTUKAN KUALITAS PEMBIAYAAN KPRS MIKRO SYARIAH BERSUBSIDI PADA BPRS - Muhammad Yusuf (STIE Indonesia Banking School, 2015)
This research will discuss the factors in determining the quality of Islamic micro finance KPRS the BPRS, the variable consists of the variable funding procedures. The purpose of the study is expected to determine and analysis which variables are more influential and significant in determining the quality of Islamic Micro financing KPRS subsidized BPRS, making Islamic micro finance subsidized KPRS channeled through the BPRS can be channeled to targeted low-income communities (MBR). While to examine the relationship socioeconomic variables with science Tawhidi using the Oneness of Allah as the source of the knowledge of good is revealed through Al - Quran and Al Hadiths in each run natural phenomenon and its contents, including the social and economic concerns of human life used methods TSR (Tawhidi String Relationship). The results of statistical analyzes and explains that the variables are more influential and significant in determining the quality of the financing, is a variable job with the highest coefficient standardized of 4,694 compared to the value of the other variable, where the variable work, divided into 3 (three) types of professions, the profession as a laborer / farmers, private sector employees and civil/military/civil service teachers.